2009
DOI: 10.1073/pnas.0903934106
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical trajectory study of H+SiH 4 reactions in full-dimensionality reveals atomic-level mechanisms

Abstract: potential energy surface ͉ reaction dynamics T he AϩBC type reactions have long served as benchmarks in the development of the kinetics and dynamics theories of chemical reactions (1-5). However, behavior of polyatomic reactions may be qualitatively different from what has been deduced from studies of atom-diatom dynamics. For example, a major reaction path, which does not follow the intrinsic reaction coordinate, has recently been found by Hase et al. (6) in their quasiclassical trajectory (QCT) study on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
(55 reference statements)
2
23
0
Order By: Relevance
“…When ZPE is included in the reactants, the results here are in reasonable agreement with the trajectory calculations of Cao et al, 66 evaluated on a much higher level ab initio PES. The cross sections initially rise with increasing energy, but become approximately constant at high energy.…”
Section: Downloaded By Australian National University On 06 May 2011supporting
confidence: 87%
“…When ZPE is included in the reactants, the results here are in reasonable agreement with the trajectory calculations of Cao et al, 66 evaluated on a much higher level ab initio PES. The cross sections initially rise with increasing energy, but become approximately constant at high energy.…”
Section: Downloaded By Australian National University On 06 May 2011supporting
confidence: 87%
“…The possible role of weak vdW interactions on reaction dynamics is an issue of great interest24567891011. Although the importance of orientation or stereodynamical effects of the long-range anisotropic interactions was realized earlier1213141516, and has recently become apparent in the emerging field of ultracold bimolecular reactions17, it is quite remarkable that the shallow vdW well2 in the entrance channel of a classic activated chemical reaction (Cl+H 2 ) can have an evident effect on the outcome of the reaction at low collision energies, which has been well recognized since the work of Skouteris et al 2.…”
mentioning
confidence: 99%
“…However, despite the exciting advances in revealing the effects of the vdW well in direct reactions dominated by the activation barrier24567891011, the role of the vdW structure in the dynamics of a complex-forming reaction dominated by a deep well is still unclear. Currently, people tend to believe that the vdW wells also exist in other types of chemical reactions.…”
mentioning
confidence: 99%
“…Silylene, SiH 2 , the prototype radical in silylene family, plays an important role in the organic silicon chemistry, [1][2][3] and it is postulated as a reactive intermediate in the manufacturing process of amorphous silicon lms by chemical vapor deposition. [4][5][6][7] The studies of SiH 2 started as early as 1967, when Dubois and co-workers observed electronic absorption spectra belonging to theX 1 A 1 -Ã 1 B 1 transition of this radical for the rst time. 8 It was not ascertained that whether the lower 1 A 1 state of the observed transition was the ground state or there was a lower-lying triplet state, as in CH 2 , would be the ground state until Milligan and Wirsam's work conrmed that the lower state of the previously observed electronic transition of singlet SiH 2 , is the ground state 9,10 and Apeloig and co-workers explained why CH 2 is a ground state triplet while SiH 2 is a ground state singlet.…”
Section: Introductionmentioning
confidence: 99%